State Responsibility And Substantive Justice: Land Acquisition For UIII Development In Depok - Putra, Gilang; Winanti, Atik (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2026)
The study finds that in Decision Number 259/Pdt.G/2021/PN Dpk, the panel of judges emphasized procedural legal certainty by declaring the claim inadmissible (niet ontvankelijke verklaard) on the grounds of a defect of parties (plurium litis consortium), resulting in the substantive issues of land ownership and possession remaining unaddressed. While the dispute was formally concluded under civil procedural law, the decision raises important concerns regarding the state's obligations to communities affected by land acquisition for public purposes. Adopting an administrative law perspective, this study argues that the procedural disposition of the case should not be construed as eliminating the state's responsibility to resolve outstanding claims stemming from the exercise of public authority in development projects. Referring to Hans Kelsen's Theory of State Responsibility, the study maintains that the procedural outcome of Decision Number 259/Pdt.G/2021/PN Dpk does not absolve the state of its duty to provide legal protection, acknowledge legitimate community interests in land, and guarantee meaningful access to justice. Accordingly, the implementation of land acquisition for public purposes should strike a balance between procedural legality and the substantive protection of community land rights to promote legal certainty, justice, and public trust.